The design of bioactive marine peptides as a HIV-1 protease inhibitor - Taufik Muhammad Fakih; Mentari Luthfika Dewi (Universitas Islam Indonesia, 2021)
AbstractBackground: Human immunodeficiency virus/acquired immunodeficiency syndrome (HIV or AIDS) is a disease related to the human immune system. Given its important role in viral replication, HIV1 protease (HIV1 PR) becomes the major therapeutic target in the treatment of AIDS. In this case, we need a dynamic aspect of molecular interactions that can demonstrate the important role of conformational variability in the design of HIV1 PR inhibitors. There are several inhibitor candidates from marine organisms, such as the LLEYSL and LLEYSI bioactive peptides produced by oysters (Crassostrea gigas).Objective: Proteinpeptide docking method was used in silico to identify, evaluate, and explore the molecular interactions between bioactive peptide molecules and HIV-1 protease macromolecules.Methods: The sequencing of bioactive peptide molecules was modeled into 3D conformation using the PEPFOLD software. The best conformation was chosen for the study of molecular interactions against HIV1 protease macromolecules using the PatchDock software. The molecular interactions formed were further observed using the BIOVIA Discovery Studio 2020 software.Results: The results of this study indicated that the LLEYSL bioactive peptide had the best affinity with an ACE score of minus 1284.70 kJ per mol.Conclusion: Bioactive peptide molecule is predicted to be a candidate for HIV1 protease inhibitor.Keywords: AIDS, HIV1 protease, bioactive peptides, protein-peptide docking, in silico Intisari Latar belakang: Infeksi human immunodeficiencyvirus/acquired immunodeficiency syndrome (HIVor AIDS) adalah penyakit yang berkaitan dengan sistem kekebalan tubuh pada manusia. Mengingat perannya yang penting dalam replikasi virus, HIV1 protease (HIV1 PR) merupakan target terapi utama dalam pengobatan AIDS. Dalam hal ini, maka diperlukan aspek dinamis dari interaksi molekuler yang dapat menunjukkan peran penting dari variabilitas konformasi dalam desain inhibitor HIV-1 PR. Terdapat beberapa kandidat inhibitor yang berasal dari organisme laut, seperti peptida bioaktif LLEYSL dan LLEYSI yang dihasilkan oleh tiram (Crassostrea gigas). Tujuan: Metode penambatan molekuler berbasis protein-peptida dilakukan untuk mengdentifikasi, mengevaluasi, dan mengeksplorasi interaksi molekuler antara molekul peptida bioaktif dengan makromolekul HIV1 protease secara in silico.Metode: Sekuensing molekul peptida bioaktif terlebih dahulu dimodelkan menjadi konformasi 3D dengan menggunakan software PEPFOLD. Konformasi terbaik dipilih untuk kemudian dilakukan studi interaksi molekuler terhadap makromolekul HIV1 protease dengan menggunakan software PatchDock. Interaksi molekuler yang terbentuk diamati lebih lanjut dengan menggunakan software BIOVIA Discovery Studio 2020.Hasil: Hasil dari penelitian ini menunjukkan bahwa peptida bioaktif LLEYSL memiliki afinitaspaling baik dengan ACE score sebesar minus 1284,70 kJ per mol.Kesimpulan:Dengan demikian, molekul peptida bioaktif tersebut diprediksi dapat dijadikan sebagai kandidat inhibitor HIV1 protease.Kata kunci : AIDS, HIV1 protease, peptida bioaktif, penambatan molekuler berbasis protein-peptida, in silico.